A new diffusion for laminar boundary layer flow of power law fluids past a flat surface with magnetic effect and suction or injection. (November 2015) - Lin, Yanhai; Zheng, Liancun; Li, Botong; Ma, Lianxi
Highlights: Steady laminar boundary flow of power law fluids past a flat surface is studied. A new nonlinear diffusion with velocity gradient and concentration is considered. The effects of magnetic fields and suction/injection are taken into account. PDEs are reduced into ODEs and solved by shooting method with Newton method. Abstract: This paper investigates steady laminar boundary layer flow of power law fluids past a flat surface with suction or injection and magnetic effects. A new nonlinear diffusion model is proposed, which takes the effects of power law viscosity on concentration fields into account by assuming that the concentration field is similar to the velocity, with a modified Fick's law of diffusion for power law fluids. The governing strongly nonlinear partial differential equations are reduced into a set of coupled ordinary differential equations and then solved numerically by the shooting technique coupled with the Runge–Kutta scheme and the Newton's method. The effects of the Hartmann number, the suction or injection parameter, the power law index, the concentration power law index, the concentration radio parameter and the generalized Schmidt number on the velocity and the concentration fields are presented graphically and analyzed in detail.